Tracking financial inclusion through deficit budget analysis in Nagaland, India - Tase, Keliihol (Religación. Centro de Investigaciones en Ciencias Sociales Humanidades desde América Latina, 2021)
The paper finds that, to achieve financial inclusion for the India’s unbanked poor is a pressing goal with perplexing obstacles. While states or union territories like Puducherry, Himachal Pradesh and Kerala announced 100% financial inclusion in all their districts, the level of financial inclusion in Nagaland remains very low. The paper finds that financial inclusion as earmarked in policies does not reach the common beneficiaries of Deficit Budgetary Government and conclude that Financial Inclusion strategy needs to be built.